Pengaruh Kualitas Pelayanan, Citra, dan Motivasi Belajar Terhadap Kepuasan Akademik Mahasiswa - Putri Titi Pertiwi; Rusdarti; Wijang Sakitri (Journal of Economic Education and Entrepreneurship Studies, 2021)
This study aimed to analyze the effect of service quality, image, and learning motivation on the students’ academic satisfaction in Faculty of Economics Universitas Negeri Semarang. The methods of data collection were questionnaires and interviews. The methods of data analysis used descriptive percentage analysis, and multiple linear regression analysis. The results of the study showed that there was a simultaneously positive effect of service quality, image, and learning motivation on students’ academic satisfaction by 48.40%. Partially service quality affected by 21.34% and image affected by 4.97%, and learning motivation had a minor and not significant effect by 2.04% on the students’ academic satisfaction. The conclusion in this study is service quality, image, and learning motivation simultaneously affect students’ academic satisfaction in Faculty of Economics Universitas Negeri Semarang year 2014.